Cyclical vomiting syndrome in children: condition missed? - Sina Aziz (Journal of the Pakistan Medical Association, 2025)
Cyclic vomiting syndrome (CVS) affects the quality of life inchildren with repeated attacks of vomiting resemblingmigraine. It is prevalent in nearly 2.3% of children.1 In 20082a consensus statement of NASPGHAN on managementpaediatric CVS was made, this is now replaced by anupdated 2025 NASPGHAN3 detailed guidelines. Includedin these guidelines are pharmacological and nonpharmacologicalpreventive management strategies, lifestyleinterventions, abortive and acute management andtreatment of comorbid conditions. Continue...